Prevalence of periodontitis in chronic heart failure patients and its relationship with NT-ProBNP: A cross-sectional study - Sonika Sharma; Deepti Mathur; Sourabh Goswami; Manoj Kumar Gupta; Pankaj Bhardwaj; Pravin Kumar; Surender Deora (Indian Heart Journal)
Background: Periodontal disease has been associated with chronic heart failure (CHF) and may be an indicator of high risk of adverse cardiovascular outcomes. To date, only few studies have been done and none from India regarding the association of periodontal disease in heart failure patients. So, this study was done to assess the prevalence of periodontitis in CHF patients and its correlation with N-terminal pro brain natriuretic peptide (NT- ProBNP). Materials and method: In this study, 154 patients with stable CHF with left ventricular ejection fraction of less than 40 % were enrolled. All subjects underwent cardiologic and dental evaluations. NT pro-BNP level was measured in all patients. The periodontal screening index was used to quantify the degree of periodontal disease. Results: Gingivitis, moderate periodontitis, and severe periodontitis were present in 48 (31.2 %), 82 (53.2 %), and 24 (15.5 %) patients, respectively. In individuals under the age of 75 years, the study found a significant association between moderate and severe periodontitis and elevated NT-proBNP levels (p < 0.05). The comparison between gingivitis and moderate/severe periodontitis was statistically significant in post hoc analysis. Conclusion: CHF patients exhibit a high prevalence of moderate and severe periodontitis. This study highlights a significant association between periodontitis severity and elevated NT-proBNP in CHF patients, underscoring a potential cardiac impact. Further research is warranted to deepen our understanding of this relationship.